A Novel GMP Protocol to Produce High-Quality Treg Cells From the Pediatric Thymic Tissue to Be Employed as Cellular Therapy - Bernaldo-de-Quirós, Esther; Cózar, Beatriz; López-Esteban, Rocío; Clemente, Maribel; Gil-Jaurena, Juan Miguel; Pardo, Carlos; Pita, Ana; Pérez-Caballero, Ramón; Camino, Manuela; Gil, Nuria; Fernández-Santos, María Eugenia; Suarez, Susana; et al. (Frontiers in Immunology, 2022)
Due to their suppressive capacity, the adoptive transfer of regulatory T cells (Treg) has acquired a growing interest in controlling exacerbated inflammatory responses. Limited Treg recovery and reduced quality remain the main obstacles in most current protocols where differentiated Treg are obtained from adult peripheral blood. An alternate Treg source is umbilical cord blood, a promising source of Treg cells due to the higher frequency of naïve Treg and lower frequency of memory T cells present in the fetus’ blood. However, the Treg number isolated from cord blood remains limiting. Human thymuses routinely discarded during pediatric cardiac surgeries to access the retrosternal operative field has been recently proposed as a novel source of Treg for cellular therapy. This strategy overcomes the main limitations of current Treg sources, allowing the obtention of very high numbers of undifferentiated Treg. We have developed a novel good manufacturing practice (GMP) protocol to obtain large Treg amounts, with very high purity and suppressive capacity, from the pediatric thymus (named hereafter thyTreg). The total amount of thyTreg obtained at the end of the procedure, after a short-term culture of 7 days, reach an average of 1,757 x106 (range 50 x 106 – 13,649 x 106) cells from a single thymus. The thyTreg product obtained with our protocol shows very high viability (mean 93.25%; range 83.35% – 97.97%), very high purity (mean 92.89%; range 70.10% – 98.41% of CD25+FOXP3+ cells), stability under proinflammatory conditions and a very high suppressive capacity (inhibiting in more than 75% the proliferation of activated CD4+ and CD8+ T cells in vitro at a thyTreg:responder cells ratio of 1:1). Our thyTreg product has been approved by the Spanish Drug Agency (AEMPS) to be administered as cell therapy. We are recruiting patients in the first-in-human phase I/II clinical trial worldwide that evaluates the safety, feasibility, and efficacy of autologous thyTreg administration in children undergoing heart transplantation (NCT04924491). The high quality and amount of thyTreg and the differential features of the final product obtained with our protocol allow preparing hundreds of doses from a single thymus with improved therapeutic properties, which can be cryopreserved and could open the possibility of an “off-the-shelf” allogeneic use in another individual.